The Impact of Corporate Governance on Capital Structure For Companies Listed on The IDX - Erlikawati, Erlikawati; Srihastuti, Eni; Awalina, Putri; Agustin, Beby Hilda (Dinasti Publisher, 2025)
This study was conducted due to the challenges in implementing good governance practices in public companies in Indonesia. Companies in Indonesia also face challenges in ownership and control of the company. Amidst the increasingly complex business world, corporate governance and decision-making regarding capital structure are becoming increasingly important. The purpose of this study is to determine how corporate governance, especially commissioner compensation, board size, and company size affect the company's capital structure. The sample of this study includes companies listed on the LQ 45 index on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The research data comes from financial reports available on the IDX website. To test the hypothesis, a two-way ANOVA analysis was used. The research findings show that there is no significant difference in capital structure related to compensation and board size. Conversely, company size shows a significant effect on variations in capital structure. In addition, there is no significant interaction between board compensation, board size, and company size in their effect on differences in company capital structure.